2022
DOI: 10.1071/an21460
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ewe behaviour around lambing time and prediction of parturition 7 days prior to lambing by tri-axial accelerometer sensors in an extensive farming system

Abstract: Context. Lamb loss and dyctocia are two major challenges in extensive farming systems. While visual observation can be impractical due to the large sizes of paddocks, number of animals and high labour cost, wearable sensors can be used to monitor the behaviour of ewes as there might be changes in their activities prior to lambing. This provides sufficient time for the farm manager to nurse those ewes that are at risk of dyctocia. Aim. The objective of this study was to determine whether the behaviour of a preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Classifier algorithms developed at the Centre for Technology Infusion (CTI), La Trobe University, using Support Vector Machine (SVM) procedures, were used to process the motion sensor data (Sohi et al 2021).…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classifier algorithms developed at the Centre for Technology Infusion (CTI), La Trobe University, using Support Vector Machine (SVM) procedures, were used to process the motion sensor data (Sohi et al 2021).…”
Section: Algorithmsmentioning
confidence: 99%
“…For our data, SVM was a good classifier as data were not linearly separable. The SVM models to classify accelerometer data streams into animal behaviour data were developed using human-verified (labelled data) that was collected from previous commercial farm studies (Sohi et al 2021). The placement and orientation of sensors attached to the sheep were the same as the validation study Sohi et al (2021).…”
Section: Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning model’s effectiveness was limited by the size of the dataset, as seen in prior works with larger datasets gathered in sheep [ 20 , 21 , 22 , 25 , 72 ]. Comparing results before and after the data unbalancing process confirmed a trade-off between accuracy and recall, a common outcome in such procedures, as indicated by the initial and final confusion matrix values illustrated in Figure 8 and Figure 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Sensors have been applied in a variety of contexts to categorize and quantify sheep behavior for different purposes. For example, sensors can be used to monitor change in ewe behavior during parturition events (licking, grazing, rumination, walking, standing, and idling) [3][4][5]. Numerous studies have demonstrated the factors that impact the accuracy, precision, recall (also known as sensitivity), F-score, and specificity of behavior classification when using sensors.…”
Section: Introductionmentioning
confidence: 99%